Fatigue failure model for fiber bundles - Zhao, Xue Ji. (2008)
In this report, a theoretical model of fatigue failure for fiber bundles with surface flaw is proposed based on the classical concept of crack growth behavior. Maximum surface flaw on each fiber in the bundle is taken as source of crack propagation. Modeling is proceeded from stress redistribution under cyclic loading to estimation of initial crack length. Statistical technique and simulation are used to study fiber bundles behavior. It is found that fatigue behavior of fiber bundles could be expressed by S-N curve, resulting in the logarithm of time-to-failure of fiber bundles being approximately linearly related to applied stress.